2016
DOI: 10.1017/jns.2016.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a plant sterol-enriched spread on biomarkers of endothelial dysfunction and low-grade inflammation in hypercholesterolaemic subjects

Abstract: Plant sterols (PS) lower LDL-cholesterol, an established risk factor for CHD. Endothelial dysfunction and low-grade inflammation are two important features in the development of atherosclerosis. Whether PS affect biomarkers of endothelial function and low-grade inflammation is not well studied. The aim of the present study was to investigate the effect of regular intake of PS on biomarkers of endothelial dysfunction and low-grade inflammation. In a double-blind, randomised, placebo-controlled, parallel-group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…In addition, clinical studies have evaluated the association between phytosterols’ consumption and inflammatory markers, such as CRP and cytokines. Although the results showed by Ras et al [213] are in aggreement with the data reported by Demonty, no changes in CRP levels were observed. In a new study conducted by Ras et al [209], in 240 hypercholesterolaemic voluntaries who consumed a low-fat spread with added phytosterols (3 g/day) for 12 weeks, no changes in any of the markers evaluated (CRP, SAA, IL-6, IL-8, TNF-α, and sICAM-1) were observed.…”
Section: Bioactive Compoundssupporting
confidence: 70%
“…In addition, clinical studies have evaluated the association between phytosterols’ consumption and inflammatory markers, such as CRP and cytokines. Although the results showed by Ras et al [213] are in aggreement with the data reported by Demonty, no changes in CRP levels were observed. In a new study conducted by Ras et al [209], in 240 hypercholesterolaemic voluntaries who consumed a low-fat spread with added phytosterols (3 g/day) for 12 weeks, no changes in any of the markers evaluated (CRP, SAA, IL-6, IL-8, TNF-α, and sICAM-1) were observed.…”
Section: Bioactive Compoundssupporting
confidence: 70%
“…In regards to inflammation, there was no significant reduction in any of the markers evaluated in the study conducted by Ras et al 54 : C-reactive protein (CRP), serum amyloid A, interleukin (IL)-6, IL-8, TNF-α, and ICAM-1. In a systematic review and meta-analysis recently published, Rocha et al.…”
Section: Introductionmentioning
confidence: 84%
“…Currently, there are available studies assessing endothelial dysfunction, arterial stiffness, diameter of the retinal vessels, and inflammation of low degree. 39 , 41 , 50 - 54 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations